ANALYSIS OF THE EFFECT OF THE ADDITION OF ALUMINUM POWDER ON POLYESTER-GLASS COMPOSITE PROPERTIES IN TENSILE AND HARDNESS TEST - Żuk, Daria; Abramczyk, Norbert; Panasiuk, Katarzyna; Dudzik, Krzysztof; Ziegler, Burkhard (Scientific Journal of Gdynia Maritime University, 2024)
The study aimed to analyse the influence of aluminum powder on the mechanical properties of polyester-glass composites. Composite materials were made of glass fibres with random fibre direction and polyester resin with the addition of aluminum powder as a filler. The strength parameters of materials obtained during the static tensile test and hardness test were compared. The results were subjected to statistical analysis, taking into account the change in the amount of filler, microstructure was also observed using optical microscopy. An analysis of the results showed that the addition of aluminum powder amounting to 2% of the weight of the composites reduces their hardness and, at the same time, the longitudinal modulus of elasticity.The addition of aluminum powder amounting to 5% and 10% of the weight of the composites increased the hardness of the composites while reducing the Young's modulus. The values of hardness measurements were subjected to statistical analyses at significance level α = 95. The Shapiro-Wilk test confirmed that the hardness variables for all tested samples were in normal distributions, and therefore the most powerful parametric tests were used to test the differences. Using the Student's t-test, it was confirmed that between pairs of variables in configurations: a standard sample with a modified sample, for all tested samples there are significant statistical differences in the distributions of hardness values. Studies have shown that the modification of the mechanical and strength properties of composite materials, through the use of an aluminum filler, makes it possible to obtain materials with variable parameters that can be useful and attractive in many new areas, depending on the application and user requirements.